Assessing the impacts and feasibility of emissions reduction scenarios in the Po Valley - Colombo, Loris; Marongiu, Alessandro; Malvestiti, Giulia; Fossati, Giuseppe; Angelino, Elisabetta; Lazzarini, Matteo; Gurrieri, Gian Luca; Pillon, Silvia; Lanzani, Guido Giuseppe (Frontiers in Environmental Science, 2023)
This study is focused on a pivotal objective: enhancing air quality and attaining pollutant concentrations in accordance with WHO guidelines. The study extensively evaluates the feasibility of reducing emissions, specifically targeting an 80% decrease in SOX, NOX, PM, NH3, and NMVOC emissions within a limited timeframe. Despite notable emission curtailments of 50% and 80%, the research reveals that recommended pollutant levels are unlikely to be met across most areas of the Po Valley region. Even when implementing the finest available technologies across various sectors, particularly within the Lombardia region, this goal remains unattainable without simultaneous reductions in activity levels. This involves diminishing factors like vehicle miles traveled, energy consumption for heating, and industrial, agricultural, and livestock production. Overall, achieving improved conforming to the new AQG limits is a multifaceted endeavor involving numerous stakeholders and diverse strategies. Successful adherence to Air Quality limits mandates the implementation of Source-Specific emissions standards at the EU level, alignment of the National Emission Reduction Directive with limits specified in the Air Quality Directive, and the formulation of comprehensive Air Quality Plans at national, regional, and local tiers.